Site-selective metallization of polymeric substrates by the hyperbranched polymer templates - Li, Peiyuan; Yang, Fang; Li, Xiangcheng; He, Chunling; Su, Wei; Chen, Jinhao; Huo, Lini; Chen, Rui; Lu, Chensheng; Liang, Lifang (Applied surface science, 2013)
•A novel convenient method for electroless copper deposition on flexible polymer based on amine polymer is reported.•The formation of modified-substrate is characterized by ATR FT-IR and CA analysis.•The formation of Pd-activated substrate is confirmed by XPS and SEM analysis.•The copper film on substrate is characterized by SEM, TEM, CA and XRD analysis. We demonstrate a simple, cost-effective and universal technique for the fabrication of copper circuit pattern on flexible polymeric substrate. This method relies on a ternary polyethylenimine-poly(acrylic acid)-substrate film incorporating palladium catalysts, which are used as adhesive interlayers for the copper metallization of flexible polymeric substrates. We demonstrated the fabrication of patterned copper films on a variety of flexible polymers with minimum feature sizes of 200μm. And the resulting copper circuit showed strong adhesion with underlying flexible polymeric substrates. The films were characterized by ATR FT-IR, contact angle, XPS, XRD, TEM and SEM. The direct patterning of metallic circuit on flexible polymeric substrate indicates great potential for the use in electronics industry.